ANALISIS TRUST BASED BRAND CREDIBILITY AND RESONANCE TERHADAP BRAND LOYALTY PRODUK FASHION MEREK ERIGO DI SOLO RAYA - Dwi Siti Sholikah; Moechammad Nasir (JURNAL LENTERA BISNIS, 2025)
This research aims to examine the impact of perceived credibility, service quality, consumer experience, and product availability on brand loyalty concerning Erigo fashion products in the Solo Raya region. The study employs a quantitative approach with an explanatory research design, utilizing questionnaires to gather data from 250 respondents who have purchased Erigo products. Data analysis was conducted using the Partial Least Square (PLS) method with the aid of SmartPLS software. The findings indicate that all independent variables positively and significantly affect brand loyalty. Perceived credibility enhances customer loyalty by fostering greater trust in the brand. Service quality contributes to heightened customer satisfaction and a stronger relationship with the company. Consumer experience facilitates memorable engagements with the brand, while product availability ensures that consumer demands are met effectively. This study underscores the critical role of these four factors in cultivating and sustaining consumer loyalty toward the Erigo brand. The study suggests that the company should focus on enhancing brand credibility, service quality, consumer interactions, and product availability to foster long-term customer loyalty.